Anuran skin and basking behavior: the case of the treefrog Bokermannohyla alvarengai (Bokermann, 1956) - Centeno, Fernanda C. [UNESP]; Antoniazzi, Marta M.; Andrade, Denis V. [UNESP]; Kodama, Roberto T.; Sciani, Juliana M.; Pimenta, Daniel C.; Jared, Carlos (Wiley-Blackwell, 2015)
We investigated the morphology of the skin and the biochemistry of the lipids in the skin secretion of Bokermannohyla alvarengai, a montane treefrog that is known to bask regularly, motionless in full sunlight for extended periods of time. Our primary goal was to identify structural and biochemical modifications that might assist this frog species to accommodate the conflicting demands for heat exchange and water balance while basking. The modulation of heat exchange in basking B. alvarengai involves changes in skin coloration. We found that this response was supported by a prominent monolayer of large iridophores, whose light reflectance property is adjusted by the response of intervening melanophores. Mucosubstances and lipid compounds, mainly consisted of saturated fatty acids and presumably secreted from granular glands, were detected on the skin of B. alvarengai. These compounds formed an extra-epidermal layer over the animal's dorsal surface that might assist in the prevention of excessive water loss through evaporation. Additionally, we found well-developed skin folds at the ventral region of the frogs that lead to an increment of surface area. This feature combined with the extensive hypervascularization, also noticed for the skin of B. alvarengai, may play an important role in water reabsorption. The suite of structural and biochemical modifications identified for the integument of B. alvarengai seems to conjugate aspects relevant to both, heat exchange and water balance, allowing for this species to explore basking as an efficient thermoregulatory strategy. J. Morphol. 276:1172-1182, 2015. © 2015 Wiley Periodicals, Inc.
Keywords: Amphibia; Anura; Integument morphology; Skin color change; Thermoregulation